2010
DOI: 10.1080/00986281003626532
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of a Psychology and Law Class on Legal Attitudes and Knowledge Structures

Abstract: Students in an undergraduate psychology and law course and an introductory psychology course completed a variety of measures, at both the beginning and end of the semester, to assess their knowledge of and attitudes toward psycholegal topics. The psychology and law course improved students' knowledge of psychological topics concerning the legal system, but it also made them more pessimistic in their attitudes and beliefs. Introductory psychology students did not show similar changes. In both classes, students'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This article builds on the work done by Smith et al (2020) in proposing amendments to the Home Office (2003) voice parade procedures through improved understanding of system variables (Wells, 1978), that is, variables that are controllable by law enforcement. Importantly, while the focus of this article is centred on using the guidelines developed for use in England and Wales, the conclusions of this body of research are relevant to all jurisdictions where earwitness evidence is admitted as evidence; this includes much of Europe, the United States, Australia, and Canada (Broeders & van Amelsvoort, 2001; Cantone, 2010; Laub et al, 2013; McGorrery & McMahon, 2017). The present article focuses on providing evidence-based recommendations for the system variables of parade size and the voice sample duration .…”
Section: Introductionmentioning
confidence: 99%
“…This article builds on the work done by Smith et al (2020) in proposing amendments to the Home Office (2003) voice parade procedures through improved understanding of system variables (Wells, 1978), that is, variables that are controllable by law enforcement. Importantly, while the focus of this article is centred on using the guidelines developed for use in England and Wales, the conclusions of this body of research are relevant to all jurisdictions where earwitness evidence is admitted as evidence; this includes much of Europe, the United States, Australia, and Canada (Broeders & van Amelsvoort, 2001; Cantone, 2010; Laub et al, 2013; McGorrery & McMahon, 2017). The present article focuses on providing evidence-based recommendations for the system variables of parade size and the voice sample duration .…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with what we have already reviewed, her research revealed that courses covered 32 topics ranging from general review and theory to criminal, civil, and broader legal issues. Laub, Maeder, and Bornstein (2010) recently found that participating in a psychology and law course enhanced students’ knowledge of psycholegal topics, but also shifted their attitudes toward the legal system, highlighting the need for instructors to be conscious of such effects. (See also Mandracchia, Shaw, & Morgan, 2013.…”
Section: Methodsmentioning
confidence: 99%
“…For example, enrolment in higher education can reduce prejudice towards social groups such as the poor (Sword and others, ) and minority groups such as gays and lesbians (Case and Stewart, ). Academic training can positively affect awareness of psychological factors and their influence on individual behaviour (Laub and others, ). Higher education affects individual choices such as the preferred number of children (fertility rate) (Yu and others, ).…”
Section: The Pervasive Influence Of Higher Educationmentioning
confidence: 99%